Analysis of Leading Sectors in Karo Regency for the 2019-2023 Period - Sembiring, Graciela Br; Selfiana Lumban Batu; Hernita Siagian (Outline Publisher, 2025)
This study aims to determine the leading and non-leading sectors in the economy of Karo Regency, to determine the sectors that have the greatest influence on Karo Regency. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS). The data included in this study are the 2019-2023 GRDP of Karo Regency at Current Prices and the GRDP of North Sumatra. Accompanied by other secondary data that are relevant to the purpose of this writing using the LQ and Shift share analysis methods. The results of this study obtained that the leading sectors are: the agriculture, forestry and fisheries sector, the transportation and warehousing sector, the accommodation and food and beverage provision sector, the government administration, defense and mandatory social security sector, the education services sector, the health services sector and social activities, and other service sectors. And the sectors that have the greatest competitiveness in Karo Regency are: the agriculture, forestry and fisheries sector.